Report from the Select Committee on the Hudson's Bay Company [electronic resource] : together with the proceedings of the committee, minutes of evidence, appendix and index. - Great Britain. Parliament. House of Commons. Select Committee on the Hudson's Bay Company. ([S.l. : s.n., 1857)
Tables. "Ordered, by The House of Commons, to be Printed, 31 July and 11 August 1857." "224. 260 -Sess. 2. 0.109 -1858." Electronic reproduction. Mode of access: Internet. 44